2013
DOI: 10.1111/ahe.12018
|View full text |Cite
|
Sign up to set email alerts
|

Equine Articular Chondrocytes on MACT Scaffolds for Cartilage Defect Treatment

Abstract: Treatment of cartilage defects poses challenging problems in human and veterinary medicine, especially in horses. This study examines the suitability of applying scaffold materials similar to those used for human cartilage regeneration on equine chondrocytes. Chondrocytes gained from biopsies of the talocrural joint of three horses were propagated in 2D culture and grown on two different scaffold materials, hyaluronan (HYAFF®) and collagen (BioGide®), and evaluated by light and electron microscopy. The equine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Areas adjacent to the defects bore crystals with especially large diameters. Furthermore, defects treated with in vitro stimulated constructs (Ponomarev et al 2014) contained chondrocytes with crystals, but not those which were treated with statically cultured chondrocytes on a biomaterial (Nürnberger et al 2013b). …”
Section: Discussionmentioning
confidence: 99%
“…Areas adjacent to the defects bore crystals with especially large diameters. Furthermore, defects treated with in vitro stimulated constructs (Ponomarev et al 2014) contained chondrocytes with crystals, but not those which were treated with statically cultured chondrocytes on a biomaterial (Nürnberger et al 2013b). …”
Section: Discussionmentioning
confidence: 99%
“…Bhardwaj and Webster to tensile testing and the data obtained showed that the maximum load that the scaffold could withstand without breaking was 17.4652 N and the modulus of elasticity was found to be 5.0875×10 8 Pa. The extension at the end of test was observed to be 1.9204 mm as shown in Figure 3.…”
mentioning
confidence: 90%
“…Collagen I, chitosan, and hyaluronic acid-based scaffolds and gels have proven to be good carriers for chondrocytes. [8][9][10][11][12][13] These scaffolds often promote the release of certain cytokines and growth factors from cells that promote the healing and regeneration of cartilage lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Chondrocytes were harvested from cartilage chips (1-2 g) taken from the talocrural joints of all horses except for the control animal. All the following steps were performed for each biopsy/horse separately as described in detail in Nürnberger et al [6]. Chondrocytes were enzymatically isolated, seeded in culture flasks and passaged when confluent.…”
Section: Transplant Generationmentioning
confidence: 99%
“…The horse is generally considered to be a good animal model for cartilage defect treatment because joint dimension as well as cartilage morphology and physiology are similar to that of humans and because horses suffer from the same degenerative and traumatic injuries [3][4][5]. A detailed characterisation of equine chondrocytes on two structurally very different MACT scaffolds has recently been published [6] ( Figure 1). The study showed that the cells reacted well and in a similar way to human chondrocytes on these materials, and that the distribution of the chondrocytes strongly depended on the material density.…”
Section: Introductionmentioning
confidence: 99%